A Study of Changing Face of Employee Compensation Practices in Public Sector Units: A Comparative Study of Compensation Practices in Public and Private Sector Industrial Enterprises (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Compensation is one the most vital functions of human resource management (HRM). The present investigation went for investigating contrasts between the public and private sector industrial enterprises of Bangladesh concerning general status of compensation practices. The measurements i.e. settled pay, adaptable pay, and advantages were analyzed as to fulfillment with compensation. The work motivation then again was contemplated utilizing the exertion and performance measurements. A few ramifications are additionally offered for general change of the compensation practices of the public and private sector industrial enterprises of India.